Participation in Public Consultations on Spatial Planning Documents. The Case of Poznań City - Kaczmarek, Tomasz; Wójcicki, Michał (Quaestiones Geographicae, 2016)
This article seeks to present the development od public participation in local spatial planning in Poland. An assessment was made of the procedure of preparing planning documents and forms of their consultation with residents. To achieve this goal, use was made of the results of a survey research conducted among participants of public consultations in Poznań in the years 2012-2014. It is stressed that it is necessary to improve the decision-making process in urban spatial planning by accommodating not only traditional but also new forms and instruments of public participation.